Surface phenomena in the structural and mechanical behaviour of solid polymers - Volynskiĭ, A. L.; Bakeev, N. F. (CRC Press, 2016)
"Surface Phenomena in the Structural and Mechanical Behaviour of Solid Polymers explores the role of various surface phenomena in the structural and mechanical behaviour of amorphous and semicrystalline polymers. This book:Discusses the development of the interfacial surface in the deformation of polymersExamines the healing of interfacial surfaces in polymersInspects the structure and properties of polymers in thin films and surface layersEvaluates the mechanism of inelastic deformation in glassy amorphous polymersInvestigates strain softening and the phenomena taking place upon deformation of polymers in active liquid mediaCovers the Rehbinder effect, or the adsorption reduction of the strength of solidsDescribes the properties of polymers in environmental or solvent crazingAnalyses the interaction of the highly developed surface of crazed polymers with diverse low- and high-molecular mass componentsAddresses the instability and self-organisation of surface layers in polymers and diverse polymer systemsPresents theoretical speculations concerning the structurally mechanical behaviour of a rigid coating on a soft substratum (RCSS) systemsAssesses the stress-strain properties of the thin surface layers of polymers and the nanometric coatings deposited on their surfacesHighlights the efficacy of the approaches developed for RCSS systems for the analysis and description of natural phenomenaDetails the applied aspects of surface phenomena in the structurally mechanical behaviour of polymersThus, Surface Phenomena in the Structural and Mechanical Behaviour of Solid Polymers provides a useful framework for the development of new and innovative polymer-based materials."--Provided by publisher.